Sever - DeStefano, Lauren (New York : Simon & Schuster BFYR, 2013)
After modern science turns every human into a genetic time bomb with men dying at age twenty-five and women dying at age twenty, teenaged Rhine finds hope for a brighter future from a surprising source.
Booklist
Booklist, December 2012
Young Adult.
Young Adult
Keywords: Genetic engineering -- Juvenile fiction; Orphans -- Juvenile fiction; Survival -- Juvenile fiction; Genetic engineering -- Fiction; Orphans -- Fiction; Science fiction; Survival -- Fiction; Genetic engineering -- Fiction; Orphans -- Fiction; Science fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Science fiction